Targeting a highly repeated germline DNA sequence for improved real-time PCR-based detection of Ascaris infection in human stool. - Nils Pilotte; Jacqueline R M A Maasch; Alice V Easton; Eric Dahlstrom; Thomas B Nutman; Steven A Williams (Public Library of Science (PLoS), 2019)
Background With the expansion of soil transmitted helminth (STH) intervention efforts and the corresponding decline in infection prevalence, there is an increased need for sensitive and specific STH diagnostic assays. Previously, through next generation sequencing (NGS)-based identification and targeting of non-coding, high copy-number repetitive DNA sequences, we described the development of a panel of improved quantitative real-time PCR (qPCR)-based assays for the detection of Necator americanus, Ancylostoma duodenale, Ancylostoma ceylanicum, Trichuris trichiura, and Strongyloides stercoralis. However, due to the phenomenon of chromosome diminution, a similar assay based on high copy-number repetitive DNA was not developed for the detection of Ascaris lumbricoides. Recently, the publication of a reference-level germline genome sequence for A. lumbricoides has facilitated our development of an improved assay for this human pathogen of vast global importance. Methodology/principal findings Repurposing raw DNA sequence reads from a previously published Illumina-generated, NGS-based A. lumbricoides germline genome sequencing project, we performed a cluster-based repeat analysis utilizing RepeatExplorer2 software. This analysis identified the most prevalent repetitive DNA element of the A. lumbricoides germline genome (AGR, Ascaris germline repeat), which was then used to develop an improved qPCR assay. During experimental validation, this assay demonstrated a fold increase in sensitivity of ~3,100, as determined by relative Cq values, when compared with an assay utilizing a previously published, frequently employed, ribosomal internal transcribed spacer (ITS) DNA target. A comparative analysis of 2,784 field-collected samples was then performed, successfully verifying this improved sensitivity. Conclusions/significance Through analysis of the germline genome sequence of A. lumbricoides, a vastly improved qPCR assay has been developed. This assay, utilizing a high copy-number repeat target found in eggs and embryos (the AGR repeat), will improve prevalence estimates that are fundamental to the programmatic decision-making process, while simultaneously strengthening mathematical models used to examine STH infection rates. Furthermore, through the identification of an optimal target for PCR, future assay development efforts will also benefit, as the identity of the optimized repeat DNA target is likely to remain unchanged despite continued improvement in PCR-based diagnostic technologies.